Sistema multiagente fuzzy para monitoramento e avaliação - Oliveira, Wedson Carlos Gomes de (Universidade Federal Rural do Semi-Árido, 2018)
Stroke is one of the biggest causes of death and disability in individuals across the globe. It is a medical emergency that has initially the appearance of symptoms abruptly on one side of the body. Stroke may be ischemic when it has artery obstruction, or hemorrhagic when it presents the factors responsible for bringing blood to the brain and the main risk factors for hypertension, atrial fibrillation, diabetes, dyslipidemia, smoking, and sedentary lifestyle. Some of these factors are directly related to people’s habits and lifestyle. Other factors such as age, race, family history and sex also influence its incidence. Thus, this study aims to develop a multi-agent fuzzy system to guide, monitor, classify and evaluate patients for primary prevention of stroke risk factors, entitled SoStroke. The system is divided into two modules, SoStroke web exclusively for the physician, responsible for classifying, evaluating, creating conduct for their patients and also monitoring their performance. Sostroke mobile is responsible for interpreting and issuing notifications on patients’ smartphones, based on context awareness. The notifications can be a tip or question and all require user responses, representing the accomplishment of the task or not. Finally, to validate SoStroke, a case study was carried out with medical specialists and professional suggestions were collected. In addition, it performed usability tests obtaining satisfactory results based on metrics of literature and expert opinion
Keywords: AVC; Computação ubíqua; Prevenção primária; Sistemas inteligentes; Intelligent system; Primary prevention; Stroke; Ubiquitous computing; CIENCIAS EXATAS E DA TERRA::CIENCIA DA COMPUTACAO